Answer:
1 - a/variable
2 - d/statistic
3 - b/population
4 - c/data
5 - e/parameter
6 - f/sample
I did comment asking if the two you'd already selected were definitely correct, but no answer was given, so I apologise if this is wrong. This is what I would put.
When multiplying with fractions you can multiply the top and the bottom independantly
5*3 = 15
1*4 = 4
so 5 * (3/4) = 15/4
Answer:
21.98
Step-by-step explanation:
C=2πr C=2d are the formulas of circumference so that would mean the diameter of the circle is 7 since 2 times the radius is the diameter. We then multiply the diameter 7 by PI to get 21.98
So the question is asking: (x-4)(x-2)
because there is a bracket in between the two expressions it means we have to multiply them together: (x-4) x (x-2)
you can break down the question into smaller parts:
x multiply x
x multiply -2
-4 multiply x
-4 multiply -2
here are the answers:
x^2 (means x squared)
-2x
-4x
8 (because when you multiply two negative numbers it makes a positive)
now you put it into an expression (this is expanding):
x^2 - 2x - 4x + 8
to simplify it you collect like terms:
x^2 - 6x + 8
The above is the answer :)
Answer:
x=±1. are the factors of the quadratic equation.
Step-by-step explanation:
Given quadratic expression, f(x)=-12x - 2x + 60x² +14x-60
Rearranging and adding the terms in the expression and equating to zero.
f(x)= 60x² -60=0
60(x² - 1) =0
The zero product property states that if the product of a⋅b=0 then either a or b equal zero or both of them must be equal to zero. This basic property helps us solve the quadratic equations like (x+2)(x-5)=0 where x =-2,5.
from the zero product property we can infer that 60≠0⇒x² - 1=0
⇒(x+1)×(x-1) = 0
⇒x=±1.
Therefore, x=±1. are the factors of the quadratic equation.